Impact of total quality management practices on financial performance of commercial banks in Nepal - Yadav, Omprakash Pd. (Pravaha, 2021)
The main objective of this study is to analyze the impact of TQM practices on the financial performance of commercial banks in Nepal. This study is based on primary as well as secondary data. Quantitative data are collected by survey method consisting of 6 likert scale questionnaires which focus on concern area of Kathmandu valley and analysis with SPSS package. Descriptive and inferential statistics tools have used to identify the relationship between management commitment, Employees involvement, Customer focus and process management with financial performance of commercial banks. In this study management commitment, employee's involvement, customer focus and process management are taken as independent variable and financial performance is taken as dependent variable. Correlation has shown that all the independent variable have significantly positive relationship with dependent variable. Among the independent variable, Employees involvement & customer focus highly positive effect on financial performance through regression analysis.